A New/Old Look at the Problem of Anesthetic Maintenance of Colonoscopy - M. V. Gabitov (Obŝaâ Reanimatologiâ, 2012)
Objective: to compare different modes of anesthesia maintenance for colonoscopy on the basis of internal audit of critical incidents. Subjects and methods. This investigation was conducted at the V. A. Negovsky Research Institute of General Reanimatology, Russian Academy of Medical Sciences, from 2009 to 2011. One hundred and fifty-six patients undergoing colonoscopy under different modes of anesthetic accompaniment were examined. Results. The authors made an internal audit of critical incidents during anesthetic accompaniment of colonoscopy on the basis of controlled sedation with propo-fol, total intravenous anesthesia, inhalational induction, and sevoflurane-maintained anesthesia. Controlled sedation with propofol was shown to have shortcomings. Conclusion. Inhalational induction and sevoflurane-maintained anesthesia are the most effective and safe method of anesthetic accompaniment. Key words: anesthesia, sevoflurane, sedation, propofol, colonoscopy, inhalational induction.